Estudo da influência de tensoativos na flotação da apatita em coluna - Mendes, Thessa Fuzaro (2021)
Froth flotation of apatite is a process based on the physico-chemical properties that differentiate the ore possessed species , which each ore has a unique chemical characteristic and crystalline structure. The selectivity of this process is based on the degree of hydrophobicity of the particle in its natural form or modified by adding reagents. The mineral particles of interest often lack hydrophobic characteristics. However, if properly conditioned, they might have their surface chemistry modified by adding reagents such as a collector, depressant, frother and pH modifier. For this reason, flotation takes place after the ore conditioning step to increase its selectivity, besides flotation is based in the bubble-particle aggregate formation combined with the surface chemistry and the size of the species contained on the system. With regard to surfactants, they are bipolar compounds consisting on a polar group and a hydrocarbon chain. These compounds are added in the flotation to generate a froth layer on the pulp, so the flotated particles can be removed. The addition of surfactants in the flotation process aims to control the bubble size, producing smaller bubbles and, consequently, increasing the probability of bubble-particle collision and providing froth stabilization. In view of the need to increase the probability of bubble-particle collision with the use of a surfactant and thereby increase the recovery of apatite in the flotation process, this work aims to investigate the capacity of seven surfactants, of different types, in reducing the bubble diameter and surface tension in the air-water-surfactant system, finding the coalescence critical concentration (CCC) of each one and check the influence of these surfactants on the apatite flotation performance in column for the system with ore of intermediate granulometry (D32= 50,86μm). This research will be carried out using the analysis of the bubble diameter , phosphorus pentoxide content and apatite recovery. To determine the size of bubbles generated, the method of direct filming and bubble sampling of the air-water and air-water-ore systems. The results showed that all surfactants were efficient in reducing surface tension and bubble diamenters, except for the cationic surfactant. It was possible to find the coalescence critical concentration for almost all surfactants used. In the ore system, there was an influence of surfactants on the different responses ( phosphorus pentoxide content and apatite recovery), however each surfactant has a different behavior. In general, the performance of ore flotation in the presence of these surfactant anylised reached market specifications (content and recovery above 30 and 60% respectively) in alkaline pH, although, the performance of ore flotation were not sufficient in acid pH. The surfactant that achieved the best index of flotation response in the studied conditions was surfactant-F (amphoteric), however, it was not the smallest bubble size. When considering the best condition of flotation process, SDBS (anionic) achieved the best quality of flotation product. It was evident that the interaction between the collector and the surfactant during the ore flotation process may not be ignored, however, further studies are needed to better understand this relationship between them.